A Zeolite Family Nonjointly Built from the 1, 3‐Stellated Cubic Building Unit. Issue 8 (29th January 2018) - Jo, Donghui; Park, Gi Tae; Shin, Jiho; Hong, Suk Bong
Abstract: From a technological point of view, the synthesis of new high‐silica zeolites is of prime importance owing to their high potential as industrial catalysts and catalyst supports. Two such materials have been synthesized which are made up of the 1, 3‐stellated cubic unit (hexahedral ([4 2 5 4 ]) bre unit) as a secondary building unit, with the aid of existing imidazolium‐based structure‐directing agents under "excess fluoride" conditions. One of them, denoted PST‐21, is the first aluminosilicate zeolite consisting of 9‐ring apertures solely; it displays exceptional activity towards steering the skeletal isomerization of 1‐butene to isobutene and bridges the gap between small‐ and medium‐pore structures. A series of hypothetical structures are also described that are nonjointly built from the bre unit; all of these structures are chemically feasible and will thus be helpful in designing the synthesis of novel zeolites containing 9‐ring and/or 10‐ring channels. Abstract : Novel construction modality : PST‐21, the first aluminosilicate zeolite containing 9‐ring channels only, and PST‐22, which has both 10‐ and 8‐ring apertures, have been synthesized using methyl‐substituted imidazolium cations under excess‐fluoride conditions. PST‐21 shows exceptional reactivity and selectivity for the isomerization of 1‐butene.